2016
DOI: 10.4103/1735-5362.194871
|View full text |Cite
|
Sign up to set email alerts
|

Twin arginine translocation system in secretory expression of recombinant human growth hormone

Abstract: Recombinant protein production in E. coli has several advantages over other expression systems. Misfolding, inclusion body formation, and lack of eukaryotic post translational modification are the most disadvantages of this system. Exporting of correctly folded proteins to the outside of reductive cytoplasmic environment through twin-arginine system could help to pass these limiting steps. Two signal sequences, TorA and SufI are used at N-terminal of human growth hormone (hGH) bearing DsbA gene sequence at C-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The study demonstrated that TorA signal sequence was more active in transporting the target protein to the culture media compared to SufI as it was confirmed in previous study which was performed by DsbA as signaling sequences. [ 23 ] These data approved previous work regarding the potential of the TAT pathway for industrial applications as well. However, most of the proteins form inclusion body and quantitative study and bioassay methods should be used in further studies to confirm the potential use of this method in industrial scale.…”
Section: Discussionsupporting
confidence: 86%
“…The study demonstrated that TorA signal sequence was more active in transporting the target protein to the culture media compared to SufI as it was confirmed in previous study which was performed by DsbA as signaling sequences. [ 23 ] These data approved previous work regarding the potential of the TAT pathway for industrial applications as well. However, most of the proteins form inclusion body and quantitative study and bioassay methods should be used in further studies to confirm the potential use of this method in industrial scale.…”
Section: Discussionsupporting
confidence: 86%
“…The signal peptide is cleaved by a signal peptidase during or shortly after substrate translocation, and the mature protein is released on the trans-side of the membrane (Freudl, 2018). Periplasmic secretion has been widely used for the production of rhGH (Alanen et al, 2015;Amaranto et al, 2021;Bagherinejad et al, 2016Bagherinejad et al, , 2018Becker & Hsiung, 1986;Browning et al, 2017;Chang et al, 1987;Chang et al, 1989;Ghorpade & Garg, 1993;Gray et al, 1985;Guerrero Montero et al, 2019;Jeiranikhameneh et al, 2017;Li et al, 2004;Matos et al, 2014;Menezes et al, 2017;Perez-Perez et al, 2020;Rigi et al, 2021;Soares et al, 2003;Soares et al, 2008;Sockolosky & Szoka, 2013;Teresa et al, 2000;Uchida et al, 1997;Zamani et al, 2016;Zhou et al, 2021). A common approach is to fuse the signal sequence to the N-terminus of rhGH for transport, and a His-tag to the C-terminus for subsequent purification.…”
Section: Periplasmic Expressionmentioning
confidence: 99%
“…Theoretically, the reduced cytoplasmic proteins are recognized as incorrectly folded and tend to be excluded by the Tat pathway. Despite this, studies have also employed the Tat pathway to export hGH to the periplasm (Alanen et al, 2015 ; Bagherinejad et al, 2016 ; Browning et al, 2017 ; Guerrero Montero et al, 2019 ; Matos et al, 2014 ). To overcome this, Robinson laboratory developed a series of bacterial strains called CyDisCo which can oxidize disulfide bonds in the cytoplasm and allow hGH to be transported by the Tat pathway (Alanen et al, 2015 ; Matos et al, 2014 ).…”
Section: Recombinant Gh / Gha P...mentioning
confidence: 99%